Education and training for strengthening school principals through an online mode approach in Lampung Utara District - Endi Rochaendi; Andi Wahyudi; Kana Safrina Rouzi; An-Nisa Apriani; Indah Perdana Sari; Dyahsih Alin Sholihah; Mufida Awalia Putri (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
Based on the data, there are still 38,688 principals who have not adjusted their administrative requirements to the Regulation of the Minister of Education and Culture of the Republic of Indonesia concerning the Assignment of the Principals. Many of them do not have a certificate (STTPL) candidate principal. To overcome this problem through community service activities, Alma Ata University conducted a Principal Strengthening Training in Lampung Province in collaboration with the Ministry of Education and Culture. This activity aims to provide certificates (STTPL) and improve principals' managerial, entrepreneurial, and supervisory skills. The implementation through Online Mode is carried out in three stages: (1) On-the-Job Training-1, (2) In-Service Training, and (3) On-the-Job Training-2, and attended by 99 principals. The learning pattern uses the U theory syntax: observation, reflection, and action to solve problems in the learning process and develop good practices. The results of the training activities include that 99 principals have received certificates (STTPL) very satisfactorily, and there has been an increase in managerial, entrepreneurial, and supervisory skills of those who have participated.